Comparison of two DRIS methods for diagnosing nutrients deficiencies in coffee trees - Partelli, Fábio Luiz; Vieira, Henrique Duarte; Monnerat, Pedro Henrique; Viana, Alexandre Pio (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to compare the nutritional diagnoses by DRIS and DRIS with the incorporation of dry matter (modified DRIS), under four criteria: all ratios between nutrients, nutrient ratios with larger variance ratio, smaller coefficient of variation, and nutrient ratios with values greater than one. Leaf concentrations of N, P, K, Ca, Mg, S, B, Cu, Fe, Mn and Zn, and the productivity of 56 organic crops of 'Conilon' coffee of the State of Espírito Santo, Brazil, were used. The frequency of the nutrient whose index was the most negative and the most positive, the correlation between the nutrient and its index, and the correlation between productivity and nutrient balance index were evaluated. DRIS and DRIS modified (DRIS-M) had provided similar diagnoses, and the four criteria of DRIS indices calculation changed the order of nutrients limitation in coffee trees. DRIS-M presents a little higher correlation between the productivity and the nutrient balance index, as well as, between nutrient concentration and its DRIS index.
Keywords: Coffea canephora; procedures of calculations; mineral nutrition